2019
DOI: 10.1084/jem.20191792
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of differential Zika and dengue virus neutralization by a public antibody lineage targeting the DIII lateral ridge

Abstract: We previously generated a panel of human monoclonal antibodies (mAbs) against Zika virus (ZIKV) and identified one, ZIKV-116, that shares germline usage with mAbs identified in multiple donors. Here we show that ZIKV-116 interferes with ZIKV infection at a post-cellular attachment step by blocking viral fusion with host membranes. ZIKV-116 recognizes the lateral ridge of envelope protein domain III, with one critical residue varying between the Asian and African strains responsible for differential binding aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 71 publications
2
24
0
Order By: Relevance
“…Germline versions of VH3-23/VK1-5 ZIKV-neutralizing Abs showed detectable binding to ZIKV and DENV1 EDIII in the nanomolar and low micromolar range. This was also previously observed for the germline version of the VH3-23/VK1-5 Ab ZIKV-116, which bound (K D s of 48.9 nm-10 μM) and neutralized ZIKV and DENV1 strains (57). This ability of germline versions of VH3-23/VK1-5 Abs to bind ZIKV contrasts with germline-reverted forms of most broadly neutralizing Abs against HIV-1, which generally do not bind HIV-1 envelope (61).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Germline versions of VH3-23/VK1-5 ZIKV-neutralizing Abs showed detectable binding to ZIKV and DENV1 EDIII in the nanomolar and low micromolar range. This was also previously observed for the germline version of the VH3-23/VK1-5 Ab ZIKV-116, which bound (K D s of 48.9 nm-10 μM) and neutralized ZIKV and DENV1 strains (57). This ability of germline versions of VH3-23/VK1-5 Abs to bind ZIKV contrasts with germline-reverted forms of most broadly neutralizing Abs against HIV-1, which generally do not bind HIV-1 envelope (61).…”
Section: Discussionsupporting
confidence: 81%
“…The EK motif, which is only present in ZIKV and DENV1 EDIII, likely contributes to initial recognition by germline Abs that leads to the tighter binding and neutralization of these two flaviviruses by VH3-23/VK1-5 Abs. The importance of E393 in the EK motif for neutralization of ZIKV strains was also previously described for the VH3-23/VK1-5 Ab ZIKV-116 (57). In contrast to ZIKV and DENV1, the lateral ridges of DENV2, DENV4, and WNV EDIIIs all contain motifs other than EK, yet still showed weak binding to at least one mature or iGL Ab by SPR.…”
Section: Discussionsupporting
confidence: 62%
“…3c-d; 4 ). Competition-binding analysis with the previously characterized ZIKV E-specific human mAbs ZIKV-117 (recognizes the E protein dimer-dimer interface in domain II on viral particles) 30 , ZIKV-116 (binds to the E protein domain III lateral ridge epitope) 31 , and ZIKV-88 (specific for the E protein fusion loop) 5 , showed that the three newly identified neutralizing mAbs ZIKV-893, - 752, and −940 recognized non-overlapping epitopes ( Fig. 4; Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…3c,d). Competition-binding analysis with the previously characterized ZIKV-E-specific human mAb ZIKV-117 (which recognizes the E protein dimer-dimer interface in domain II of the viral particles) 30 , ZIKV-116 (which binds to the E protein domain III lateral ridge epitope) 31 and ZIKV-88 (which is specific for the E protein FL) 5 showed that the three identified in mice that were treated with the indicated mAb-encoding RNA formulations (40 μg per mouse) on day −1 and challenged with ZIKV on day 0 was determined using ELISA. The dots show measurements from individual mice; n = 5 mice per group were analysed and data represent one experiment, except for ZIKV-117, for which n = 10 mice per group were analysed.…”
Section: (Supplementarymentioning
confidence: 99%